Simulação molecular da adsorção de gases em materiais nanoporosos: captura, caracterização e armazenamento - Gonçalves, Daniel Vasconcelos (2018)
Molecular simulation techniques were applied to predict gas adsorption in nanoporous materials. Three problems were approached. In the first problem, we studied the H2S adsorption in activated carbon. A value for H2S-carbon interaction was proposed from calorimetric data. The proposed forcefield parameter was validated by predicting H2S capture on two activated carbons (RB4 and Desorex K43). This is the first theoretical study of this nature. The impact of the presence of CH4 and CO2 on H2S adsorption was also evaluated. Multicomponent adsorptions (H2S/CH4, H2S/CO4 and H2S/CH4/CO2) were calculated in three sizes of slit-pores of carbon. We observed a cooperative effect in which CO2 improves H2S adsorption in the 8.9 Å pore size. The analysis of energy distribution and the positioning of the molecules inside the pore evidenced this improvement. In the second problem, we adsorption properties of carbon structures resulting from the oxidative process predicted by reactive Molecular Dynamics (rMD) have been investigated. Simulation features, like the type of molecular model and the boundary condition, were evaluated. Isotherms and enthalpies of adsorption of N2 and Ar on carbon surfaces with different degrees of etching were calculated. These results were compared to experimental data. The structure with 25% of gasified atoms reproduced the adsorption on activated carbons made from different precursors and through different processes. Structures predicted by rMD presented superior performance in prediction of adsorption experimental data. In the third problem, we investigated eight representative metal-organic frameworks (MOFs) for natural gas storage. Adsorbed amounts of pure methane and its mixtures with CO2 and H2O at 5.8 and 65 bar at 298 K were calculated within the limits specified for natural gas. MOFs without open metal sites were minimally influenced by the concentrations of CO2 and H2O. However, the interaction with these species on MOFs with open metal sites proved to be harmful. We found that concentrations as low as 25 ppm of water can reduce the delivered volume of methane by more than 20%. A detailed analysis of the adsorption mechanisms leading to deactivation is also presented.